Financial intermediation and financial inclusion of poor households: Mediating role of social networks in rural Uganda - George Okello Candiya Bongomin; Joseph Mpeera Ntayi; John C. Munene; Charles Malinga Akol (Cogent Economics & Finance, 2017)
The paper examined the mediating role of social networks in the relationship between financial intermediation and financial inclusion of poor households in rural Uganda. The paper used SPSS (statistical package for social scientist) and applied MedGraph program (Excel version 13), Sobel test, and Kenny & Baron guideline to test for the mediating role of social networks in the relationship between financial intermediation and financial inclusion. Quantitative data were collected from a total sample of 400 poor households living in rural Uganda who were randomly selected for this study. The findings revealed that social networks partially mediate in the relationship between financial intermediation and financial inclusion of poor households in rural Uganda. Besides, social networks and financial intermediation have significant and positive impacts on financial inclusion of poor households in rural Uganda. This implies that some effects of financial intermediation on financial inclusion go through social networks to cause an impact on financial inclusion of poor households in rural Uganda. Therefore, financial institutions such as banks and microfinance institutions should develop financial products and services that promote social networking among poor households in rural Uganda. In addition, they should advocate for participation by poor households in existing village associations and social organizations so as to develop wide social networks. This will help them to gain access to scarce and vital information about available financial services like credit.
Keywords: 330; financial inclusion; social networks; financial intermediation; rural Uganda; poor households; banks and microfinance; financial intermediaries